Discourse and regulation failures: The ambivalent influence of NGOs on political organizations - Matthias Georg Will; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2014)
In the last decades, NGOs have become an important participant in the work of political organizations (e.g., national authorities, the EU or the UN). This development brings many opportunities and also some challenges, including discourse failure which is one of the topics discussed in this paper. We present a case study that illustrates the interdependence of discourse failure and regulations failure. We conclude that discourse failure is frequently not merely an accidental by-product, but rather, a non-intended consequence of deliberate NGOs' campaigns. We make particular note of probable discourse failure when campaigns attempt to deal with complex issues in an environment rife with wide-spread prejudices and where the NGO's work is transparent. In this situation, regulation failure may be consequent upon discourse failure. We present collectively binding commitments for NGOs and binding services enforced by political organizations to prevent discourse failure. In conclusion, we argue that the field of political economy can benefit from this challenging environment if it systematically researches the interdependencies between discourses and regulations. – – In den letzten Jahrzehnten kamen NGOs als wichtige Akteure im politischen Regelsetzungsprozess hinzu (z. B. in der EU, der UN und auch auf den nationalen Ebenen). Aus dieser Entwicklung ergeben sich für die Zivilgesellschaft vielfältige Chancen, allerdings auch einige Herausforderungen. Zu den Herausforderungen zählt unter anderem Diskursversagen, woraus häufig Regulierungsversagen resultiert. Der Beitrag präsentiert eine Fallstudie, die das Zusammenspiel aus Diskurs- und Regulierungsversagen aufzeigt. Das Beispiel illustriert, dass Diskursversagen nicht nur ein zufälliger Nebeneffekt von öffentlichen Diskursen ist, sondern eine nicht-intendierte Folge zielgerichteter Kampagnen von NGOs sein kann. Insbesondere Kampagnen, die sich mit komplexen Themen auseinandersetzen, über die es in der Öffentlichkeit weitverbreitete Vorurteile gibt, neigen zu Diskursversagen. Durch transparente Kampagnen seitens der NGOs wird dies sogar begünstigt. Zur Überwindung dieser Defizite stellt der Beitrag verschiedene Bindungsmechanismen für NGOs und Bindungsservices durch Behörden und Politik vor. Abschließend zeigt der Beitrag auf, dass die Politische Ökonomik davon profitieren kann, wenn sie systematisch das Zusammenspiel zwischen Diskurs und Regulierung erforscht.
urn:nbn:de:gbv:3:2-26190
Keywords: 330; Discourse Failure; Regulation Failure; NGO; Political Organizations; National Authorities; EU; UN; Self-Commitments; Political Economy; Diskursversagen; Regulierungsversagen; NGO; Politische Organisationen; Behörden; EU; UN; Selbst-Bindung; Politische Ökonomik